2007
DOI: 10.1021/jp0743471
|View full text |Cite
|
Sign up to set email alerts
|

Higher Energy States in the CO Dimer:  Millimeter-Wave Spectra and Rovibrational Calculations

Abstract: New extensive millimeter-wave measurements of the 12 C 16 O dimer have been made, and more than 300 new spectral transitions have been observed in the frequency range 81-135 GHz. A joint analysis of these and previous millimeter-wave data yielded the precise location of 33 new energy levels of A + symmetry and 20 levels of A -symmetry. These energy levels are located at 8-18 cm -1 above the zero-point level. Some of them belong to already known stacks, and others make up 9 new stacks of the dimer. Newly determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
83
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(100 citation statements)
references
References 29 publications
(116 reference statements)
16
83
1
Order By: Relevance
“…Laboratory data have clarified later a spectroscopic problem of these unsuccessful searches. The extensive millimeter-wave (MMW) studies of the CO dimer (Surin et al 2007) have shown that the radio astronomical search of this complex was based on frequencies which cannot be unambiguously attributed to (CO) 2 . In the case of the CO-paraH 2 complex, the interstellar search was outside the correct frequency position of the most promising R(0) line, as later identified by the first MMW study of CO-paraH 2 (Pak et al 1999), and only the weaker Q(1) line was correctly tuned.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory data have clarified later a spectroscopic problem of these unsuccessful searches. The extensive millimeter-wave (MMW) studies of the CO dimer (Surin et al 2007) have shown that the radio astronomical search of this complex was based on frequencies which cannot be unambiguously attributed to (CO) 2 . In the case of the CO-paraH 2 complex, the interstellar search was outside the correct frequency position of the most promising R(0) line, as later identified by the first MMW study of CO-paraH 2 (Pak et al 1999), and only the weaker Q(1) line was correctly tuned.…”
Section: Introductionmentioning
confidence: 99%
“…Similar experiments have been carried out also for the isotopic species of the CO dimer, (C 18 O) 2 and ( 13 CO) 2 , with the OROTRON in the MMW region, and two very closely located "isomers" of A + symmetry were reported (Surin et al 2007). The energy gaps between the "Cbonded" and "O-bonded isomer" are found to be 0.638 and 1.287 cm −1 for (C 18 O) 2 and ( 13 CO) 2 (Surin et al 2007), respectively.…”
Section: The Co Dimer (Co)mentioning
confidence: 60%
“…The very low bending vibration is an indication of the extreme floppiness of the CO dimer. The value of 3.731 cm −1 is almost the same as, or even slightly lower than, the rotational J = 1-0 transition frequency, Surin et al (2007).  American Chemical Society, 2007.…”
Section: The Co Dimer (Co)mentioning
confidence: 70%
See 2 more Smart Citations